Brand, Promotion and Innovation: Their Impact on Motorcycle Purchasing Decisions - Waworuntu, Ahmad Yusdarwin; Hajar, Hajar; Otoluwa, Narto Irawan (Advances: Jurnal Ekonomi & Bisnis, 2023)
The objective of this study is to examine the impact of brand awareness, promotional activities, and product innovation on consumer purchasing behavior in the context of motorbikes within Makassar City. The present study employed the survey method to investigate a sample of 80 individuals, selected by the incidental sampling technique. The data was obtained by administering a questionnaire that had undergone rigorous testing to ensure its validity and reliability. The process of data analysis involves the application of multiple regression analysis to assess the validity of a given hypothesis. The findings of the study indicate that there is a strong and statistically significant relationship between brand awareness and consumer purchase behavior. Promotion exerts a favorable and substantial impact on consumer purchasing decisions. Furthermore, it is worth noting that product innovation exerts a favorable and substantial impact on consumer purchasing behavior.